ROS-mediated waterlogging memory, induced by priming, mitigates photosynthesis inhibition in tomato under waterlogging stress - Niu, Lifei; Jiang, Fangling; Yin, Jian; Wang, Yinlei; Li, Yankai; Yu, Xiaqing; Song, Xiaoming; Ottosen, Carl-Otto; Rosenqvist, Eva; Mittler, Ron; Wu, Zhen; Zhou, Rong (Frontiers in Plant Science, 2023)
stage did not show positive mitigative effects. The plants of 'LA4440' with priming showed lower peroxidase (POD) activity and proline content but higher H2O2 content than that without priming under waterlogging stress. Under waterlogging stress with priming as compared to without priming, SODCC2 was downregulated in two tomatoes, and AGR2 and X92888 were upregulated in 'MIX-002' but downregulated in 'LA4440'.Overall, the two tomato genotypes exhibited distinct photosynthetic, ROS and osmotic regulatory mechanisms responding to the waterlogging stress. Waterlogging priming can induce stress memory by adjusting stomatal conductance, sustaining ROS homeostasis, regulating osmotic regulatory substances and key gene expressions mediated by H2O2, and thus alleviate the damage on tomato photosynthesis when waterlogging reoccurred.